AB0634 Characterisation of sle patients who underwent cardiovascular surgery. (12th June 2018) - Kawamoto, T.; Matsushita, S.; Amano, H.; Minowa, K.; Asai, Y.; Yamaji, K.; Amano, A.; Tamura, N.
Abstract : Background: SLE is characterised by alternate occurrences of flares and remissions throughout its course. During these flares, immune complexes are excessively produced and deposited in affected tissues. Previous reports suggest that immune complexes deposited in the blood vessels, atrioventricular valves, and other associated components of the heart cause disorders in these tissues. Although, the characteristics of patients in whom tissue injuries progress and ultimately require surgery have not been clarified. 1 Objectives: Heart diseases are categorised into valvular disease, ischaemic heart disease, and aortic aneurysm. This study was conducted to determine whether there was a correlation between the activity of SLE and the progress and aggravation of heart disease in each category. Methods: Of the 2707 patients who were diagnosed with SLE at Juntendo University Hospital from 2012–2017, 35 underwent cardiac surgery. Six patients met the exclusion criteria, and thus, 29 patients were included. Patients with infectious endocarditis and those in whom SLE had not been diagnosed prior to surgery were excluded. Indices for SLE activity were anti-DNA Ab and CH50. Peak and bottom values of these indices before surgery were recorded, and the values obtained during the pre-surgery 180 day period were compared with those that had been determined prior to this period. Results: The mean disease duration at the time of cardiac surgery was 24.2 years. The cardiac diseases were heart valve disease (V) in 10, ischaemic heart disease (I) in 7, and aortic aneurysm (A) in 12 patients. The integrated values obtained by the activity indices, anti-DNA Ab, and disease duration were 14 020 for V, 32 966 for I, and 29 444 for A. Thus, there was a tendency for values to be slightly lower in the heart valve disease category. The peak/bottom values for CH50 and anti-DNA Ab in the pre-surgery 180 day period were no different from those obtained prior to this period. Investigation of anti-phospholipid antibodies indicated that the rates of positive result for either CLβ2 GPI, anti-CL antibodies, or LA were 60% for V, 28% for I, and 33% for A, and thus, higher in the heart valve disease category. All patients were treated with steroids, and five patients (17.2%) of the 29 used immunosuppressants. This rate tended to be lower than the previous frequency of the combined use of immunosuppressive drugs at our hospital (onset:18.4%, first flare 33.3%). 2 Conclusions: There is a possibility that the long-term duration of SLE may lead to cardiac disease requiring surgery. The integrated value for DNA Ab was lower in the heart valve disease category; therefore, the presence of anti-phospholipid antibodies may be a risk factor for valvular disease. The low frequency of combined use of immunosuppressants in SLE patients with cardiovascular manifestations requiring surgery, suggest the possibility that treatment with a single steroid may require heart surgery. References: [1] Yasuhiro Sakaguti, Sachio Kawai, Ryozo Okada, et al. Immunohistochemical study of the endomyocardial biopsy of Systemic Lupus Erythematosus. Journal of Cardiology. 1995;25:181–188 [2] Kentaro Minowa, Hirofumi Amano, Yoshinari Takasaki, et al. Disease flare patterns and predictors of systemic lupus erythematosus in a monocentric cohort of 423 Japanese patients during long-term follow-up: The JUDE study. Mod Rheumatol. 2017;27:72–76 Acknowledgements: none Disclosure of Interest: None declared